THE IMPORTANCE OF HUMAN RESOURCE MANAGEMENT IN THE COMPANY - DASMADI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2022)
This writing paper aimed for knowing role management resource man in organization . Writing paper this use method review literature (library research). From discussion could concluded that management source power man have three function that is function managerial , function operational and functional reach aim organization in a manner integrated . Whereas Duty from management source power man is procurement of staff, development of its human resources , managing compensation , take care safety and health work , take care connection labor and industrial relations . Aim main management source power man is for Upgrade contribution resource humans ( employees ) against organization . this _ could understood that all activity organization in reach the goal depends on the people who manage it organization the . because _ that employee must managed with good so that could help organization in reach aim organization that has determined . For reach aim from management source power man performed by HR managers , managers line and outsourcing .